Free Press : journal of the Campaign for Press and Broadcasting Freedom. (London : CPBF.)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : 9 Poland Street, London W1
Met ‘supplement on media treatment of lesbians and gay men’
Engels
Periodiek